The Right to Be Parents : LGBT Families and the Transformation of Parenthood - Ball, Carlos A. (Book collections on Project MUSE., 2012)
"In 1975, California courts stripped a lesbian mother of her custody rights because she was living openly with another woman. Twenty years later, the Virginia Supreme Court did the same thing to another lesbian mother. In ordering that children be separated from their mothers, these courts ruled that it was not possible for a woman to be both a good parent and a lesbian. The Right to be Parents is the first book to provide a detailed history of how LGBT parents have turned to the courts to protect and defend their relationships with their children. Carlos A. Ball chronicles the stories of LGBT parents who, in seeking to gain legal recognition of and protection for their relationships with their children, have fundamentally changed how American law defines and regulates parenthood. Each chapter contains riveting human stories of determination and perseverance as LGBT parents challenge the widely-held view that having a same-sexual orientation, or that being a transsexual, renders individuals incapable of being good parents. To this day, some courts are still not able to look beyond sexual orientation and gender identity in order to fairly apply legal principles in cases involving LGBT parents and their children. Yet on the whole, stories are of progress and transformation: as a result of these pioneering LGBT parent litigants, the law is increasingly recognizing the wide diversity in American familial structures. The Right to be Parents explores why and how that has come to be"--Provided by publisher.